UV‐Induced Photopatterning of the Thermoresponsive Properties of a Poly(ethylene glycol)methylether acrylate‐co‐poly(N‐isopropylacrylamide) Hydrogel - Qian‐Pu Cheng; Nikolaj K. Mandsberg; Pavel A. Levkin; Shan‐hui Hsu (Small Structures)
Photopatterning offers a versatile and precise approach for modifying surface properties, making it a valuable technique in material design. Recent research demonstrates that polymer swelling can significantly enhance photodegradation, facilitating topographical patterning. Herein, this concept in stimuli‐responsive hydrogels is explored, focusing on the thermoresponsive poly(ethylene glycol) methylether acrylate‐co‐poly(N‐isopropylacrylamide) (PPEGA–PNIPAM) hydrogel. Surprisingly, it is observed that UV exposure not only partially degrades the hydrogel but also diminishes its thermal responsiveness. This effect enables selective deactivation of responsive properties of the PPEGA–PNIPAM, allowing for spatially defined variations in thermomechanical behavior through photolithography. By using these spatial differences, the hydrogel is programmatically transformed into a thermoresponsive actuator via a single‐step photopatterning process, demonstrating a potential application of UV‐induced change of thermoresponsiveness. Furthermore, incorporating gelatin methacrylate enhances biocompatibility, suggesting new possibilities for developing thermoresponsive bioactuators. Thus, the results demonstrate the potential of UV‐induced modulation of stimuli‐responsive properties of hydrogels and present new opportunities for creating multifunctional materials with tailored properties.